Pengembangan Bahan Ajar Kemampuan Dasar Mengajar Berorientasi Case Methode untuk Meningkatkan Keterampilan Abad 21 Mahasiswa - Ade Haerullah; Said Hasan; Jailan Sahil; Ermin Ermin (Peneliti.net, 2022)
This research is important to be carried out in the Basic Teaching Ability course in the Biology Education Study Program, FKIP Unkhair because this course is one of the cores that support a graduate to become a prospective biology teacher. The purpose of this research is to produce case-oriented teaching materials to improve the 21st century skills of students in the Basic Teaching Skills course. This type of research is research and development with the ADDIE development model. The results showed that the results of the validation of the syllabus on the content aspect presented had a validation level of 95.33, the category was very valid, the discussion aspect had a validation level of 98.00 and the time aspect obtained was 98.00. It can be concluded that the three aspects are considered very good and suitable for use in the learning process with an average percentage of 97.11. Furthermore, at the evaluation stage, a limited test was conducted to determine the effectiveness of using case-oriented teaching materials to improve students' 21st century skills. The trial was conducted on second semester students of the Khairun University biology education study program. The test results show that there is an increase in the 21st century skills of students after learning by using case-oriented teaching materials